The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5603/fmc.2015.0003
|View full text |Cite
|
Sign up to set email alerts
|

Does morphine administration affect ticagrelor conversion to its active metabolite in patients with acute myocardial infarction? A sub-analysis of the randomized, double-blind, placebo- -controlled IMPRESSION trial

Abstract: Does morphine administration affect ticagrelor conversion to its active metabolite in patients with acute myocardial infarction? A sub-analysis of the randomized, double-blind, placebo--controlled IMPRESSION trial ABSTRACT Background. Therapy with aspirin and one of the platelet P2Y12 receptor inhibitors, preferably ticagrelor or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although the underlying mechanism of these findings was not investigated in detail, it seems most likely that morphine impairs absorption of ticagrelor [39]. Moreover in the subanalysis of the IMPRESSION study, we did not find any evidence that the extent of ticagrelor conversion to AR-C124910XX is affected by morphine administration [41]. Decreased exposure to AR-C124910XX in the morphine arm compared with the placebo arm of the study was most likely caused by a proportional attenuation of exposure to the parent drug.…”
Section: Morphine and Novel Oral P2y12 Inhibitorsmentioning
confidence: 56%
“…Although the underlying mechanism of these findings was not investigated in detail, it seems most likely that morphine impairs absorption of ticagrelor [39]. Moreover in the subanalysis of the IMPRESSION study, we did not find any evidence that the extent of ticagrelor conversion to AR-C124910XX is affected by morphine administration [41]. Decreased exposure to AR-C124910XX in the morphine arm compared with the placebo arm of the study was most likely caused by a proportional attenuation of exposure to the parent drug.…”
Section: Morphine and Novel Oral P2y12 Inhibitorsmentioning
confidence: 56%
“…Strong CYP3A inducers and inhibitors greatly affect pharmacokinetics of ticagrelor and its active metabolite, thus their co-administration with ticagrelor is contraindicated 19 , 20 . In healthy volunteers the bioavailability of AR-C124910XX ranges from 35% to 40% of ticagrelor plasma concentration, whereas in patients with AMI it may be as low as 21% during the initial hours of treatment 8 , 9 , 21 . Although ticagrelor may increase bioavailability of some statins, currently there are no data indicating that any of the medications routinely used for the treatment of ACS may affect metabolism of ticagrelor 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although ticagrelor may increase bioavailability of some statins, currently there are no data indicating that any of the medications routinely used for the treatment of ACS may affect metabolism of ticagrelor 22 . This also applies to morphine, the elementary analgesic used to relive chest pain in patients with ACS 21 . Therefore, it remains obscure what causes this discrepancy in the bioavailability of AR-C124910XX between healthy subjects and patients with ACS.…”
Section: Introductionmentioning
confidence: 99%
“… 16–18 The negative impact of morphine on the intestinal absorption has been proposed as an explanation for the observed interactions, while no evidence was found in support of the influence of morphine on conversion of ticagrelor into its active metabolite. 18 19 Importantly, STEMI, as opposed to NSTEMI, has also been postulated to affect ticagrelor pharmacokinetics. Franchi et al 20 reported that ticagrelor exposure is attenuated and delayed in patients with STEMI receiving morphine and opioid-naive STEMI subjects.…”
Section: Introductionmentioning
confidence: 99%